KETERSEDIAAN BUAH DAN SAYUR DALAM KELUARGA SEBAGAI STRATEGI INTERVENSI PENINGKATAN KONSUMSI BUAH DAN SAYUR ANAK USIA PRASEKOLAH - Erlisa Candrawati; Wiwin Wiarsih; Sukihananto Sukihananto (Universitas Tribhuwana Tunggadewi, 2014)
Pre-school aged children is a risk group for poor fruit and vegetable intake. Dietary behavior and patterns are established during pre-school years and influenced by parents. The study aim is to determine the association between home availability of fruit and vegetable and its consumption among pre-school aged children. A cross sectional design with descriptive correlation was used to 89 family with pre-school aged children. It showed statistically significant relationship of food control (p value < 0,05) with a fruit and vegetable consumption pre-school aged children. Health education and counseling about parental feeding practices needs to be done as promotion and prevention intervention